THE CHARACTERIZATION ANALYSIS OF ROB HALL IN EVEREST: NEVER LET GO FILM 2015 - Risna Budiarti; Nani Ronsani Thamrin (University of Kuningan, 2016)
This research focuses on Rob Hallâ€™s characterizations and moral values found in â€œEverest: Never Let Goâ€ Film. The aims of this research are to find out Rob Hallâ€™s characterizations portrayed in the Film Everest: Never Let Go and the moral values of the Film. The researcher used the theory about psychological analysis (based on Sigmund Freud in Schultz, 2005) to find out Rob characters through his words or sentences in script of Everest; Never Let Go Film and semiotics theory (based on Roland Barthes, 1968, 1990, 1991) to find out the characteristics of Rob Hall through pictures or signs which show his character in Film â€œEverest: Never Let Goâ€ with print screen of each pictures or signs, and theory of moral value based on George and Uyanga (2014). Qualitative descriptive method was used by the researcher to find out the characteristic of Rob Hall in Everest: Never Let Go Film and the moral values of Rob Hall characterized in the Film. As result, the researcher found 6 characterizations of Rob Hall in Everest: Never Let Go Film, those are Honest, Sociable, Responsible, Assertive, Attentive, and Pessimistic. While, the moral values from this Film was that a leader should be able to support, keep, help, open, responsible, honest, assertive, wise attitude, sacrifice, and direct their team towards better.Keywords: Characterization Analysis, Rob Hall, Everest: Never Let Go Film, Pyschological Analysis, Semiotics, Moral Value